TOXIC EPIDERMAL NECROLYSIS INDUCED BY CARBAMAZEPINE: A CASE STUDY - Laskar, Jahirul Islam; Chakravarty, Pinaki; Dewan, Babul (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Objectives: The objective of this case study is to evaluate the importance of detection, assessment, and reporting of an adverse drug reaction and to improve the medication perseverance. Methods: This is an observational type of case report which was observed and analyzed in Silchar Medical College and Hospital on regular ward rounds. Results: A case report of toxic epidermal necrolysis due to carbamazepine (CBZ) administration by a 47-year-old male patient who presented as a follow-up case of ischemic stroke. Causality assessment of the event done with Naranjo’ causality assessment scale suggests to be Probable.â€ Conclusion: Daily, CBZ is being increasingly prescribed for control of pain in neuralgias and diabetic neuropathy, apart from control of seizures. Awareness about the drugs implicated in life-threatening drug reactions will help physicians in preventing them by cautious use of the drugs. Moreover, proper counseling to the patient regarding the use of medications is of utmost importance, in such life-threatening conditions where treatment guidelines remain indistinct.Â